2005
DOI: 10.2485/jhtb.14.130
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Collagen IV .ALPHA.1 to .ALPHA.6 Chains in Basement Membranes of Odontogenic Tumors

Abstract: Type IV collagen, the major component of basement membrane (BM), demonstrates a stage-and position-specific distribution of its isoforms during tooth development. To determine its localization in BM of odontogenic neoplasms, immunohistochemistry using six anti-(IV) chain-specific monoclonal antibodies was performed. Expression of 1(IV)/ 2(IV) and 5(IV)/ 6(IV) chains was stronger in the desmoplastic than in ordinary ameloblastomas. The adenomatoid odontogenic tumor distinctly expressed these chains in BM of cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Differential expression of α(IV) chains in BMs of benign and malignant odontogenic tumors have been studied and the authors suggested that modification and remodeling of these molecules occur during odontogenic tumor progression 28,29) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expression of α(IV) chains in BMs of benign and malignant odontogenic tumors have been studied and the authors suggested that modification and remodeling of these molecules occur during odontogenic tumor progression 28,29) .…”
Section: Introductionmentioning
confidence: 99%
“…chains isoform were performed in mouse tooth germ and in odontogenic tumors independently 27,28,29) . In current study, we exam- (Fig.5, f-k).…”
mentioning
confidence: 99%
“…Odontogenic tumors constitute a clinically significant group of jawbone neoplasms in the Asian region and are therefore a subject of considerable research [14][15][16][17][18][19][20][21][22][23][24][25] . Among the most well-studied are ameloblastomas [14][15][16][17][18][19] , adenomatoid odontogenic tumor 15,20) , keratocystic odontogenic tumor [21][22][23] and calcifying cystic odontogenic tumor [24][25] . These works have enumerated the clinicopathologic characteristics and clarified the various signaling molecules implicated in the development of the various tumor entities [15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the most well-studied are ameloblastomas [14][15][16][17][18][19] , adenomatoid odontogenic tumor 15,20) , keratocystic odontogenic tumor [21][22][23] and calcifying cystic odontogenic tumor [24][25] . These works have enumerated the clinicopathologic characteristics and clarified the various signaling molecules implicated in the development of the various tumor entities [15][16][17][18][19][20][21][22][23][24][25] . Limited work has been published on Notch signaling proteins in the squamous odontogenic tumor 26) .…”
Section: Introductionmentioning
confidence: 99%